Effect of the Number of Supporting Implants on Mandibular Photoelastic Models with Different Implant-Retained Overdenture Designs - Celik, Gozde; Uludag, Bulent (My University, 2014)
Purpose: The purpose of the study was to evaluate the effect of the number of supporting implants and different retentive mechanisms on load transfer characteristics of mandibular overdentures.